Digital Disruption in Teaching and Testing Assessments, Big Data, and the Transformation of Schooling - Wyatt-Smith, Claire; Lingard, Bob; Heck, Elizabeth (Critical Social Thought, 2021)
This book provides a significant contribution to the increasing conversation concerning the place of big data in education. Offering a multidisciplinary approach with a diversity of perspectives from international scholars and industry experts, chapter authors engage in both research- and industry-informed discussions and analyses on the place of big data in education, particularly as it pertains to large-scale and ongoing assessment practices moving into the digital space. This volume offers an innovative, practical, and international view of the future of current opportunities and challenges in education and the place of assessment in this context.